Peningkatan Keterampilan bagi Pengelola dan Anggota Badan Usaha Milik Desa di Desa Amokuni, Kecamatan Ranomeeto Barat, Kabupaten Konawe Selatan, Sulawesi Tenggara - Arifuddin Mas’ud; Sapto Raharjo; Weka Gusmiarty Abdullah; Emilia Nurdin; Santiadji Mustafa (Institut Pertanian Bogor, 2021)
The objective of this community service activity are to increase knowledge and skills to managers and members of Amokuni Village Owned Enterprise (Bumdes Amokuni) regarding business management, added value, determining the cost of goods manufactured (HPP), and creative marketing strategies. Activities carried out include socialization, extention, training and mentoring. The result of this service activity was that the knowledge and skills of the managers and members of Bumdes Amokuni have increased. Increased knowledge was meant in terms of business management, increasing the added value of freshwater resources, HPP determining and creative marketing strategies for freshwater fish products to be produced. Improved skills were in the form of skills in making business management concepts, processing pomfret and tilapia into shredded fish and fishbone sticks with 5 flavors (original taste, BBQ, spicy sweet, balado, and roasted corn), HPP determining, and marketing diversified products freshwater fish online and offline.